Respuesta :
Answer:
c = (3 f)/y - (12 m)/y
Step-by-step explanation:
Solve for c:
8 m + (2 c y)/3 = 2 f
Subtract 8 m from both sides:
(2 c y)/3 = 2 f - 8 m
Divide both sides by (2 y)/3:
Answer: c = (3 f)/y - (12 m)/y
The solution for c in the given equation is [tex]c = \frac{3f-12m}{y}[/tex]
From the question,
The given equation is 2/3cy+8m =2f
To solve for c in the equation,
First, let us write the equation properly
The equation written properly is
[tex]\frac{2}{3} cy+8m=2f[/tex]
Now, to solve for c
First, multiply through by 3
That is,
[tex]3\times \frac{2}{3} cy+3\times 8m=3\times 2f[/tex]
This becomes
[tex]2cy + 24m = 6f[/tex]
Now, subtract 24m from both sides of the equation
[tex]2cy + 24m -24m = 6f -24m[/tex]
Then, we get
[tex]2cy = 6f-24m[/tex]
Now, divide both sides of the equation by 2y
[tex]\frac{2cy}{2y}= \frac{6f-24m}{2y}[/tex]
∴ [tex]c= \frac{6f-24m}{2y}[/tex]
Then, we can write that
[tex]c = \frac{2(3f-12m)}{2y}[/tex]
∴[tex]c = \frac{3f-12m}{y}[/tex]
Hence, the solution for c in the given equation is [tex]c = \frac{3f-12m}{y}[/tex]
Learn more here: https://brainly.com/question/24609368